Systematic review and meta-analysis of the diagnostic accuracy of ductoscopy in patients with pathological nipple discharge. Issue 6 (23rd March 2016) - Waaijer, L; Simons, J M; Borel Rinkes, I H M; van Diest, P J; Verkooijen, H M; Witkamp, A J
Abstract: Background: Invasive surgery remains the standard for diagnosis of pathological nipple discharge (PND). Only a minority of patients with nipple discharge and an unsuspicious finding on conventional breast imaging have cancer. Ductoscopy is a minimally invasive alternative for evaluation of PND. This systematic review and meta-analysis was designed to evaluate the diagnostic accuracy of ductoscopy in patients with PND. Methods: A systematic search of electronic databases for studies addressing ductoscopy in patients with PND was conducted. Two classification systems were assessed. For DSany, all visualized ductoscopic abnormalities were classified as positive, whereas for DSsusp, only suspicious findings were considered positive. After checking heterogeneity, pooled sensitivity and specificity of DSany and DSsusp were calculated. Results: The search yielded 4642 original citations, of which 20 studies were included in the review. Malignancy rates varied from 0 to 27 per cent. Twelve studies, including 1994 patients, were eligible for meta-analysis. Pooled sensitivity and specificity of DSany were 94 (95 per cent c.i. 88 to 97) per cent and 47 (44 to 49) per cent respectively. Pooled sensitivity and specificity of DSsusp were 50 (36 to 64) and 83 (81 to 86) per cent respectively. Heterogeneity between studies was moderate to large for sensitivity (DSany : I 2 = 17·5 per cent; DSsusp : I 2 = 37·9 per cent) and very large for specificity (DSany : I 2 = 96·8 per cent; DSsusp : I 2 = 92·6 per cent). Conclusion: Ductoscopy detects about 94 per cent of all underlying malignancies in patients with PND, but does not permit reliable discrimination between malignant and benign findings. Abstract : Optimization of tissue sampling needed